2019
DOI: 10.1111/bcp.13885
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system effects of the histamine‐3 receptor antagonist CEP‐26401, in comparison with modafinil and donepezil, after a single dose in a cross‐over study in healthy volunteers

Abstract: Aims:In previous studies, the histamine-3 receptor antagonist CEP-26401 had a subtle effect on spatial working memory, with the best effect seen at the lowest dose tested (20 μg), and a dose-dependent disruption of sleep. In the current study, 3 lowdose levels of CEP-26401 were compared with modafinil and donepezil. Methods: In this double-blind, placebo-and positive-controlled, randomized, partial 6-way cross-over study, 40 healthy subjects received single doses of placebo, CEP-26401 (5, 25 or 125 μg) or moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…The outcome of the test is the average speed of the moving circle as a percentage of the maximum speed of the circle. In previous studies, CNS-stimulant compounds such as caffeine (60 mg), moda nil (200 mg), dexamphetamine (20 mg) and methylphenidate (average 20 mg) improved average adaptive tracking by approximately 1.6%, 34 1.8%, 29 4.2%, 15 and 2.2%, 30 respectively. For CNS-depressant compounds, such as benzodiazepines, an impairment of adaptive tracking has been demonstrated.…”
Section: Functional Pharmacodynamic Neurocart Assessmentsmentioning
confidence: 86%
See 4 more Smart Citations
“…The outcome of the test is the average speed of the moving circle as a percentage of the maximum speed of the circle. In previous studies, CNS-stimulant compounds such as caffeine (60 mg), moda nil (200 mg), dexamphetamine (20 mg) and methylphenidate (average 20 mg) improved average adaptive tracking by approximately 1.6%, 34 1.8%, 29 4.2%, 15 and 2.2%, 30 respectively. For CNS-depressant compounds, such as benzodiazepines, an impairment of adaptive tracking has been demonstrated.…”
Section: Functional Pharmacodynamic Neurocart Assessmentsmentioning
confidence: 86%
“…Volunteers were instructed to stand comfortably on a rm surface with their feet slightly apart and eyes closed for 2 minutes. In previous studies, CNS-stimulant compounds demonstrated reductions in body sway; for example, moda nil (200 mg), dexamphetamine (20 mg) and clinical doses (average 20 mg) of methylphenidate reduced body sway by approximately 35% 29 , 19.4% 15 and 36.8%, respectively. 30 Conversely, CNS-depressant compounds such as benzodiazepines are associated with increased body sway; for example, diazepam (10 mg) increased body sway by 119%.…”
Section: Functional Pharmacodynamic Neurocart Assessmentsmentioning
confidence: 89%
See 3 more Smart Citations